Thermal diagnosis system of belt conveyors - Goncharov K.A. (Научно-технический вестник Брянского государственного университета)
Belt conveyors are one of the most difficult objects of technical condition diagnostics due to the interaction of elements of the work process of various genesis on extended sections of the routes: bulk cargo — elastic load-carrying belt — rigid load-bearing structures. Differences in the nature of the origin and the features of the mechanical operation of these elements suggest the presence of a differentiated approach to diagnosing the technical condition of belt conveyors when operating with the use of specific equipment. At the same time, in modern industrial conditions, diagnostic methods based on new or previously unused physical phenomena are widely used. The article is the first to propose a system for thermal diagnostics of units, assemblies and elements of belt conveyors, based on the results of a number of experimental studies. The advantages and disadvantages of thermal diagnostics of transporting machines in motion are shown. The basic provisions of thermal diagnostics are proposed, which make it possible to harmoniously integrate the proposed system into a well-established set of measures for monitoring the technical condition of belt conveyors at the stages of installation and operation in the form of additional recommendations and reporting documents. The results of experimental studies of the working processes of belt conveyors by the method of thermal diagnostics are generalized and element-by-element recommendations for conducting thermal control are developed, combined into a general method.